Israel Education: Agreeing to Disagree. Issue 1 (2nd January 2023) - Gringras, Robbie
ABSTRACT: Following the lead of Israel Education: A Philosophical Analysis, Gringras first explores the idea of complexity in Israel Education, suggesting that inconsistencies are due more to emotional complexity than to the intellectual complexity of the subject matter. Due to these ideological and emotional complexities, Israel has become a wedge issue in the Jewish community abroad. Different perspectives, and different attitudes muddy the waters where disagreement undermines a "sacred" approach. Instead Israel educators should no longer aim to "transmit a broad … commitment" to anything but to the argument itself. The paper goes on to explicate how a pedagogy of argument might benefit Israel education. By centering the disagreement rather than the consensus, we invite the learner into an active involvement in their identity development that includes a dynamic engagement with Zionism's questions and Israel's answers. This approach does not suggest one stops teaching information about Zionism and Israel; it recommends altering its purpose. The educator would look to teach as much information the students might need in order to engage in a healthy argument about the topic. An ongoing commitment to holding a growth mindset, to learning multiple contrasting viewpoints, and to having the confidence and enthusiasm to argue for their perception of the collective good might describe the behavior of the ideal graduate: someone who enjoys a good argument about Israel.